Peningkatan Keterampilan Guru Mengadakan Video Pembelajaran Melalui Kegiatan iHT Dengan Aplikasi Zoom Cloud Meeting - darwin sianturi (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2021)
The purpose of this study is to improve the skills of teachers in making learning videos through iHT activities with the Zoom Cloud Meeting Application. This research is School Action Research (PTS). The research subjects were 18 subject teachers at SMAN 1 Siborongborong. Data collection techniques were observation and documentation techniques. Data validation with triangulation technique. The data analysis method in this study used qualitative data analysis. The results showed that iHT activities with the Zoom Cloud Meeting Application were proven to be able to improve the skills of teachers in making learning videos. Increasing the results of the assessment of the skills of teachers at SMAN 1 Siborongborong making learning videos in the initial conditions with an average score of 45.11 and included in the Less (K) category, increasing in the first cycle with an average value of 70.16 and entering the Enough category (C) and in the second cycle with an average value of 90.95 and included in the Good category (B).